(untitled) (Modern Problems of Metallurgy, 2019)
A large share in the overall energy balance emphasizes the place and importance of crushing processes in human life, therefore crushing hard and brittle materials is considered by destroying their original structure by impact and erasing crushers with hinged hammers, namely: splitting - hitting hammers on the material (for it the impact on the moving mass of the material stage is characteristic, it leads mainly to splitting); spalling - the impact of material from the baffle plate (which is characterized by a blow to the motionless mass of the machine, which leads mainly to spalling); erasing - erasing the material in the baffle plate and grate, as well as in the collision of material particles with each other. In hammer mills, the material particles are destroyed due to their splitting as a result of impact (ingress) and abrasion. The effective conduct of impact-washing crushing is associated with the transfer of energy consumption in the direction of direct grinding. Therefore, the task of the work was to find out the laws of the energy consumption of the crushing process depending on the ratio of the impact of impact damage and friction destruction methods, as well as changes in the crushing material strength when analyzing the operation of a hammer crusher. The useful work spent on crushing consists of the work of the impact Aуд and the work of friction Aтер, namely the ratio of these two stages of the destruction process is a prerequisite - the total and specific energy consumption for the whole process. The destruction by impact (splitting) occurs when the energy of elastic deformation, accumulated by the body, goes into the surface energy of the formation of a new surface. Friction - wiping destruction occurs due to accumulation of destructive stresses in infinitely thin surface layers of material particles, as a result of which material is removed in the form of a superfine fraction. Since the wiping process proceeds in stages with the accumulation of destructive stress in the ultrathin layer of material, the ultimate strength for this process tends to the theoretical value due to small volumes of accumulation and destruction. This is due to the minimum possible number of structural defects for an infinitely small volume of material. The paper presents the dependence for comparing the influence of two types of destructive load: impact destruction and destruction by friction for processes with different levels of dispersion of the material being crushed to enable the application of the crushing method.